Research progress on the mechanisms of interleukin and chemokine families in driving calcium oxalate nephrolithiasis formation - Liang, Fujie; Guo, Fuyou; Liu, Runjun; Wang, Xiang (Frontiers in Immunology, 2025)
Calcium Oxalate Nephrolithiasis is a globally prevalent urological disorder, with its pathogenesis involving multiple mechanisms such as inflammatory responses, oxidative stress, crystal-cell interactions, macrophage polarization, and fibrosis. In recent years, the multidimensional regulatory roles of interleukins (ILs) and chemokines in stone formation have garnered increasing attention. Pro-inflammatory interleukins, such as IL-1β, may promote crystal deposition, oxidative stress, and renal tubular epithelial cell injury by activating signaling pathways including NLRP3 inflammasome, NF-κB, and MAPK. In contrast, anti-inflammatory interleukins, by stimulating M2 macrophage polarization and suppressing crystal adhesion and oxidative damage, exhibit nephroprotective effects. Notably, IL-6 demonstrates unique bidirectional regulatory properties. Chemokines play critical roles in recruiting immune cells, amplifying inflammatory responses, modulating crystal-cell interactions, and sustaining the fibrosis-stone vicious cycle. The CXCL12/CXCR4 axis has emerged as a potential hub in regulating crystal autophagy and fibrotic progression. Additionally, miR-124-3p overexpression inhibits pro-inflammatory factor expression and promotes M2 macrophage polarization, while the IL-6/MCP-1 axis may reverse this suppression via a negative feedback network. This review integrates the multidimensional regulatory mechanisms of interleukins and chemokines in Calcium Oxalate Nephrolithiasis and proposes three novel hypotheses: the dynamic regulatory model of IL-6, the MCP-1-mediated fibrosis-stone vicious cycle, and the IL-6/MCP-1/miR-124-3p negative feedback loop.